Management Strategy For The Palagan Bojongkokosan Museum To Improve The Quality Of Service In Sukabumi Regency - Fitriya Roswanti (Dinasti Publisher, 2024)
This research aims to analyze and improve the management strategy of the Palagan Bojongkokosan Museum in an effort to improve the quality of services in Sukabumi Regency. This research uses a descriptive-analytical method with a qualitative approach, involving various data collection techniques such as observation, interviews and documentation studies.